The moderating effects of Islamic spiritual intelligence on the relationship between financial, human, and social capital, and business success of Muslim micro-entrepreneurs / Awang Moslem Awang Annuar - Awang Annuar, Awang Moslem (2022)
Using Resource Based Theory, Emmons’ Spiritual Intelligence Theory, and Theory of The Growth of The Firm as the underlying theories, the main objective of this research is to determine the moderating effects on the relationship between financial capital, human capital, and social capital, and business success of Muslim micro-entrepreneurs. Numerous studies have found that financial capital, human capital, and social capital are important factors in company success, but little is done from an Islamic perspective. There has been little research on the success of Muslim small and medium-sized companies (SMEs) in the past. Islamic entrepreneurship is not only underrepresented in relevant entrepreneurship literature, but it is also disregarded and ignored by scholars. Studies have shown that there is also a relationship between entrepreneur success and spiritual intelligence, but the variables, definitions and scope of spiritual intelligence differ.